Use hand sanitisers compatible with our skin - Goh, Choon Fu; Long, Chiau Ming * (New Straits Times Press (M) Bhd., 2020)
LETTER: The surge of Covid-19 cases reminds us again about the importance of hand hygiene and the sanitisation of our surroundings with the use of disinfectants. Our body parts, especially our skin, are consistently exposed to disinfectants, including hand sanitisers.